La lúdica como estrategia metodológica, para potenciar el uso de reglas ortográficas en los estudiantes de cuarto grado de la Unidad Educativa Particular San Gerardo en el período 2017-2018 - Pullaguari Suarez, Diana del Cisne (2018)
The research, The playful as methodological strategy to enhance the use of orthographic rules in fourth graders of the Unidad Educativa Particular San Gerardo in the 2017-2018 period, general aims: strategies methodological leisure, for the proper use of the spelling rules in students in the fourth grade of the Unidad Educativa San Gerardo in the 2017-2018 period. Descriptive study, quasi-experimental design, using methods: scientist, observational, synthetic, deductive, inductive and hermeneutic, which allowed information and structure research; the technique: the survey questionnaire as an instrument. The diagnostic procedure in the theoretical foundation, design, implementation and evaluation of the workshop; the population was 15 students and 4 teachers of the fourth degree. As a result, improved the use of orthographic rules in students. In conclusion, applying the playful as methodological strategy during the teaching-learning process the use of spelling rules